2013
DOI: 10.1111/ejn.12297
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical increase in survival of newborn neurons in the dentate gyrus of mice with constitutive depletion of serotonin

Abstract: Increased adult neurogenesis is a major neurobiological correlate of the beneficial effects of antidepressants. Indeed, selective serotonin (5-HT) re-uptake inhibitors, which increase 5-HT transmission, enhance adult neurogenesis in the dentate gyrus (DG) of the hippocampus. However, the consequences of 5-HT depletion are still unclear as studies using neurotoxins that target serotonergic neurons reached contradictory conclusions on the role of 5-HT on DG cell proliferation. Here, we analysed two genetic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 45 publications
6
70
0
Order By: Relevance
“…For 5-HT2A receptors, labeling revealed a dense staining in the hilus, whereas 5-HT2B (Diaz et al, 2013) and 5-HT2C receptors mostly mark adult granule cells (Klempin et al, 2010). 5-HT3 receptor mRNA expression was seen in hilar interneurons (Tecott et al, 1993) that was confirmed by in situ hybridization (Diaz et al, 2013). We hypothesize that the distinct actions of receptor subtypes could mediate the homeostasis of serotonin signaling in the 5 hippocampus.…”
Section: Pharmacological 5-ht Receptor Targeting Studies and Baselinementioning
confidence: 60%
See 4 more Smart Citations
“…For 5-HT2A receptors, labeling revealed a dense staining in the hilus, whereas 5-HT2B (Diaz et al, 2013) and 5-HT2C receptors mostly mark adult granule cells (Klempin et al, 2010). 5-HT3 receptor mRNA expression was seen in hilar interneurons (Tecott et al, 1993) that was confirmed by in situ hybridization (Diaz et al, 2013). We hypothesize that the distinct actions of receptor subtypes could mediate the homeostasis of serotonin signaling in the 5 hippocampus.…”
Section: Pharmacological 5-ht Receptor Targeting Studies and Baselinementioning
confidence: 60%
“…Their expression pattern varies with 5-HT1A receptor immunoreactivity found on type-1 to type-2b cells in the SGZ as well as on interneurons. For 5-HT2A receptors, labeling revealed a dense staining in the hilus, whereas 5-HT2B (Diaz et al, 2013) and 5-HT2C receptors mostly mark adult granule cells (Klempin et al, 2010). 5-HT3 receptor mRNA expression was seen in hilar interneurons (Tecott et al, 1993) that was confirmed by in situ hybridization (Diaz et al, 2013).…”
Section: Pharmacological 5-ht Receptor Targeting Studies and Baselinementioning
confidence: 68%
See 3 more Smart Citations